2010
DOI: 10.1093/ndt/gfq528
|View full text |Cite
|
Sign up to set email alerts
|

Luteolin ameliorates cisplatin-induced acute kidney injury in mice by regulation of p53-dependent renal tubular apoptosis

Abstract: These results indicate that cisplatin induces acute kidney injury by regulation of p53-dependent renal tubular apoptosis and that luteolin ameliorates the cisplatin-mediated nephrotoxicity through down-regulation of p53-dependent apoptotic pathway in the kidney.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
63
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(69 citation statements)
references
References 32 publications
5
63
0
1
Order By: Relevance
“…Chemotherapy leads to single and double DNA strand breaks, most often followed by cell death. Recent studies have shown the important role of apoptosis in the pathogenesis of cisplatin testicular (Arjumand et al, 2011;Kang et al, 2011) Thus, together with other herbal extracts, TT reduces apoptosis of cisplatin by decreasing the number of apoptotic cells that can be considered as the antioxidant activity or diuretic effect of TT.…”
Section: Discussionmentioning
confidence: 99%
“…Chemotherapy leads to single and double DNA strand breaks, most often followed by cell death. Recent studies have shown the important role of apoptosis in the pathogenesis of cisplatin testicular (Arjumand et al, 2011;Kang et al, 2011) Thus, together with other herbal extracts, TT reduces apoptosis of cisplatin by decreasing the number of apoptotic cells that can be considered as the antioxidant activity or diuretic effect of TT.…”
Section: Discussionmentioning
confidence: 99%
“…All mice were individually housed under a constant temperature (24°C) and 12-h light/dark cycle, fed the AIN-76 semipurified diet for a 1-week acclimation period, and subsequently divided randomly into three groups and fed a normal diet (ND, n = 10), high-fat diet (HFD, n = 13, 20% fat and 1% cholesterol), or HFD with 0.005% (weight for weight) luteolin (LU, n = 13; Sigma-Aldrich, St. Louis, MO) for 16 weeks. The dose of luteolin was based on previous in vivo studies (9)(10)(11)(12). All experimental diets were prepared every week and stored at 24°C.…”
Section: Animalsmentioning
confidence: 99%
“…Natural phenolics, such as hesperidin, rutin, silymarin, and genistein, have been shown to ameliorate cisplatin-mediated nephrotoxicity (Kang et al, 2011;Sahu, Kuncha, Sindhura, & Sistla, 2013). Moreover, quercetin prevented the nephrotoxic activity of cisplatin without affecting its anti-tumour activity (Sanchez-Gonzalez, Lopez-Hernandez, Perez-Barriocanal, Morales, & Lopez-Novoa, 2011).…”
Section: Introductionmentioning
confidence: 99%